외상후 스트레스 장애 증상의 심각도와 억제 통제 결함의 관계: 수면의 질과 우울의 이중매개효과 - 김주영; 김은경; 윤진웅 (Singyŏng chŏngsin ŭihak, 2024)
Objectives This study investigates the mediating effects of sleep quality and depression on the relationship between post-traumatic stress disorder (PTSD) symptom severity and inhibitory control deficit among psychiatric patients. Methods A total of 189 psychiatric patients completed questionnaires on PTSD symptom severity by using the Korean version of the Impact of Event Scale-Revised; they answered questions on sleep quality based on the Korean version of the Pittsburgh Sleep Quality Index, and answered questions on depression based on the Korean-Beck Depression Inventory-II. They were also tested to measure inhibitory control deficit by using the Stroop Task. Regression analysis and the bootstrap sampling method were conducted for data analyses. Results The major findings of this study are as follows. First, PTSD symptom severity predicted inhibitory control deficit. Secondly, depression significantly mediated the relationship between PTSD symptom severity and inhibitory control deficit, but did not affect sleep quality. Lastly, the sequential mediating effect of sleep quality and depression was significant in the relationship between PTSD symptom severity and inhibitory control deficit. Conclusion These results suggest that sleep quality and depression should be considered in the pathway from PTSD symptom severity leading to inhibitory control deficit. Therefore, addressing sleep quality and depression in PTSD intervention may help prevent the development of inhibitory control deficit. KCI Citation Count: 0